EFEK SUPLEMENTASI MULTIVITAMIN MINERAL TERHADAP KADAR HEMOGLOBIN DAN HEMATOKRIT MAHASISWI TPB IPB - Angga Hardiansyah; Rimbawan Rimbawan; Ikeu Ekayanti (Food and Nutrition Society of Indonesia, 2013)
The objective of this study was to analyze effect of multivitamin mineral supplementation to hemoglobin and hematocrit concentration of Bogor Agricultural University First Common Year female students. Design of this study was the quasi experimental, double blind, with number of subjects were 28 female students devided into two group. The intervention group consisted of 15 subjects, received supplement syrup 15 ml per day for eight weeks.The control group consisted of 13 subjects received placebo syrup. Data collected by interviewing subjects used questionnaire, physical examination, and blood biomarkers. The results of statistical test (paired sample t-test) showed that there were no significant increase in hemoglobin and hematocrit concentration respectively in both intervention and control groups (p>0.05). However, on a subset of subjects anemia, the hemoglobin and hematocrit in the intervention group tended to increase larger than the control group.